Intellectual property, COVID-19, and the next pandemic : diagnosing problems, developing cures / edited by Haochen Sun, Madhavi Sunder. - Sun, Haochen; Sunder, Madhavi (Cambridge University Press, 2024)
This volume assesses the role of intellectual property in pandemic times through lessons learned from COVID-19. Authored by an international roster of experts, chapters diagnose causes for the inequitable distribution of lifesaving COVID-19 vaccines and offer concrete suggestions for reform. From delinking vaccine development from monopoly rights in technology, to enhanced legal requirements under national and international law for sharing publicly funded technologies, to requiring funding from rich nations to former colonies to build local vaccine manufacturing capacity in low and middle-income countries (including those in Africa), this work highlights timely IP reforms that prepare us for the next pandemic. This title is also available as Open Access on Cambridge Core.